Bioinspired engineering of fusogen and targeting moiety equipped nanovesicles - Wang, Lixue; Wang, Guosheng; Mao, Wenjun; Chen, Yundi; Rahman, Md Mofizur; Zhu, Chuandong; Prisinzano, Peter M.; Kong, Bo; Wang, Jing; Lee, Luke P.; Wan, Yuan (Nature Communications, 2023)
Cell-derived small extracellular vesicles have been exploited as potent drug vehicles. However, significant challenges hamper their clinical translation, including inefficient cytosolic delivery, poor target-specificity, low yield, and inconsistency in production. Here, we report a bioinspired material, engineered fusogen and targeting moiety co-functionalized cell-derived nanovesicle (CNV) called eFT-CNV, as a drug vehicle. We show that universal eFT-CNVs can be produced by extrusion of genetically modified donor cells with high yield and consistency. We demonstrate that bioinspired eFT-CNVs can efficiently and selectively bind to targets and trigger membrane fusion, fulfilling endo-lysosomal escape and cytosolic drug delivery. We find that, compared to counterparts, eFT-CNVs significantly improve the treatment efficacy of drugs acting on cytosolic targets. We believe that our bioinspired eFT-CNVs will be promising and powerful tools for nanomedicine and precision medicine.